Strategies for reforming initial vocational education and training in Europe : final report of the project Leonardo da Vinci/Transnational Pilot Projects: Multiplier-effect, Strand III.3a Sharpening Post-16 Education Strategies by Horizontal and Vertical Networking (1997-2000) ; SPES-NET - Stenström, Marja-Leena [Herausgeber]; Lasonen, Johanna [Herausgeber] (Institute for Educational Research, 2000)
"This book is the final report of the Leonardo da Vinci projekt SPES-NET (Sharpening Post-16 Educationa Strategies by Horizontal and Vertical Networking), the multipliereffect project of the earlier Post-16 Strategies project. SPES-NET was carried out in collaboration between fourteen partners representing researchers, policymakers, administrators and teacher educators from thirteen countries (Austria, Belgium, Denmark, England, Estonia, Finland, France, Germany, Greece, Hungary, Norway, Scotland and Spain). The project focussed on European reform strategies adopted with the aim of improving the quality of vocational education and training as regards links between VET and working life, access to higher education, curriculum reform and teacher education. The project was a response to the challenge of identifying a European dimension of parity between academic/general education and vocational education and training." (Editor, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; Berufsausbildung; Arbeitswelt; LEONARDO; Berufsbildungspolitik; Bildungsreform; Image; Evaluation; Fallbeispiel; Österreich; Belgien; Dänemark; Estland; Finnland; Frankreich; Bundesrepublik Deutschland; Griechenland; Ungarn; Norwegen; Spanien; England; Schottland